Influence of Ketogenic Diet and Phenytoin Sodium on Isoniazid Induced Epilepsy in Wistar Rats - Ramachandran, Somasundaram; Sravanthi, Satya; Manthena, Sri Ramya; Liza, Undru; Amala, Masa (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The current research was set up to estimate the influence of ketogenic diet in combination with phenytoin sodium on isoniazid induced epilepsy in rats. Methods: In this work 30 rats were used with weight range of 150-200gms were selected and divided into five groups. Group -1(Positive control), Group – II (Negative control), Group – III (Standard), Group – IV (Ketogenic diet), Group – V (Ketogenic diet + Standard). The doses of isoniazid, phenytoin sodium, ketogenic diet were selected and the work was executed for a period of 30 days. Results: At the end of the study animals were sacrificed to collect brain for estimating GABA levels in different groups. Results indicated that, there is a notable rise in levels of GABA which helps in reducing seizure latency when the ketogenic diet was added to that of standard drug. Conclusion: The change in levels of GABA when compared to the ketogenic diet alone and standard suggest that ketogenic diet along with standard drug may produce antiepileptic activity by increasing the levels of GABA in isoniazid induced epilepsy in rats.
Keywords: Epilepsy; Ketone diet; Isoniazid; Phenytoin; GABA